Interaction of cationic antimicrobial peptides with Mycoplasma pulmonis. Issue 20 (28th August 2013) - Park, Ho Jin; Kang, Ki Mo; Dybvig, Kevin; Lee, Bok Luel; Jung, Yong Woo; Lee, In Hee
Abstract : We investigated the mode of action underlying the anti‐mycoplasma activity of cationic antimicrobial peptides (AMPs) using four known AMPs and Mycoplasma pulmonis as a model mycoplasma. Scanning electron microscopy revealed that the integrity of the M. pulmonis membrane was significantly damaged within 30 min of AMPs exposure, which was confirmed by measuring the uptake of propidium iodine into the mycoplasma cells. The anti‐mycoplasma activity of AMPs was found to depend on the binding affinity for phosphatidylcholine, which was incorporated into the mycoplasma membrane from the growth medium and preferentially distributed in the outer leaflet of the lipid bilayer. Abstract : We examine the action mechanism of antimicrobial peptides against mycoplasma. The mechanism relies on interaction of antimicrobial peptides with membrane lipids. Binding to phosphatidylcholine is critical for their anti‐mycoplasma activity.